ISLAMISASI BANTEN: DINAMIKA SEJARAH, BUDAYA, DAN POLITIK DALAM PENYEBARAN ISLAM DI UJUNG BARAT JAWA - Siti Mubadi Awaliyah; Muhammad Abdul Azis; Abdul Mu’ti; Maftuhsujana (Jurnal Riset Multidisiplin Edukasi, 2025)
The entry of Islam in Banten is an important part of history in the archipelago. The spread of Islam in Banten is not only through a military approach, but also through a peaceful approach that adapts to the local culture. This article contains about the history of the entry of Islam in Banten, With a focus on how Islam spread to the Banten region and who were the figures in the spread.This research was carried out using a literature study of text studies by collecting various related sources. This article describes the process of the entry of Islam into Banten, and when did Islam enter the Banten area. Hopefully this article will provide an overview and add to our insight into the Islamic history of the archipelago and can contribute to forming a better civilization.